Enhancing iron biogeochemical cycling for canga ecosystem restoration: insights from microbial stimuli - da Silva, Rayara do Socorro Souza; Cardoso, Aline Figueiredo; Angelica, Rômulo Simões; Bitencourt, José Augusto P.; Moreira, Julio Cezar Fornazier; Lucheta, Adriano Reis; Prado, Isabelle Gonçalves de Oliveira; Candela, Dalber Ruben Sanchez; Gastauer, Markus (Frontiers in Microbiology, 2024)
The microbial-induced restoration of ferruginous crusts (canga), which partially cover iron deposits and host unique ecosystems, is a promising alternative for reducing the environmental impacts of the iron mining industry. To investigate the potential of microbial action to accelerate the reduction and oxidation of iron in substrates rich in hematite and goethite, four different microbial treatments (water only as a control - W; culture medium only - MO; medium + microbial consortium - MI; medium + microbial consortium + soluble iron - MIC) were periodically applied to induce iron dissolution and subsequent precipitation. Except for W, all the treatments resulted in the formation of biocemented blocks. MO and MI treatments resulted in significant goethite dissolution, followed by precipitation of iron oxyhydroxides and an iron sulfate phase, due to iron oxidation, in addition to the preservation of microfossils. In the MIC treatment, biofilms were identified, but with few mineralogical changes in the iron-rich particles, indicating less iron cycling compared to the MO or MI treatment. Regarding microbial diversity, iron-reducing families, such as Enterobacteriaceae, were found in all microbially treated substrates. However, the presence of Bacillaceae indicates the importance of fermentative bacteria in accelerating the dissolution of iron minerals. The acceleration of iron cycling was also promoted by microorganisms that couple nitrate reduction with Fe(II) oxidation. These findings demonstrate a sustainable and streamlined opportunity for restoration in mining areas.